KUALITAS PELAYANAN KADER POSYANDU LANSIA DALAM MELAKUKAN PELAYANAN PADA LANJUT USIA - Prabasari, Ninda Ayu; Novita Sari, Nia; Jalus, Fransiska (JPK : Jurnal Penelitian Kesehatan, 2024)
Basic level health services aimed at elderly people who are starting to experience the aging process are very necessary in society. Posyandu for the elderly is a place that can detect health problems for the elderly. Its implementation requires health cadres who can invite elderly people to take part in elderly posyandu activities. Cadre competency and experience is one of the things that a cadre must have. The aim of the research is to determine the quality of service for elderly Posyandu cadres in providing services to the elderly. Descriptive research with an elderly population at the Matahari Senja Elderly Posyandu, taking samples by purposive sampling with a sample size of 30 respondents fulfilling the inclusion criteria. Data collection uses a questionnaire. The majority of respondents were female, 70%, the majority of cadre service quality was in the good category, 18 (60%) people. Three indicators of service quality, namely work discipline and service facilities, have a good category with a percentage of 94% and service communication has a good category with a percentage of 97%. The quality of service for cadres is good if the cadres in elderly services need insight, skills related to elderly health problems besides that a work ethic, responsibility, work discipline and good communication are needed.